Pigmentation and mineral composition of different Azolla species. - Ruschel, Alaídes Puppin; Filho, Austrelino Silveira; Santos, Alberto Baeta dos; Zimmermann, Francisco José P. (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was conducted to study pigmentation (chlorophyl and anthocyanin) and mineral composition (P, K, Ca, Mg, Zn, Cu, Mn, Fe) of different Azolla ecotypes representatives of Azolla caroliniana, Azolla filiculoides, Azolla microphylla, and Azolla mexicana species, growing under field conditions. The experiment was repeated at different periods (June, August, September and October, 1985), in the same area, in randomized blocks, with five replicates. There was no correlation between the level of plant nutrients and Azolla pigmentation. Dry matter weight and relative growth rate (RGR) were different among species and period of year. The highest relative growth rates varied from 0.232 and 0.466 g/g of inoculum.day-1, for periods of low (June) and high (October) growth, respectively. There was an effect of plant species and period of the year on P, K, Mg and Ca absorption; however absorption of micronutrients was only affected by the period of the year. Azolla pigmentation seems to be linked to a genetic plant character.